Islamic Educational Thought: Zakiyah Darajat's Perspective - Nasikhin Nasikhin; Abdul Ghofur; Rokhmadi Rokhmadi; Ulul Albab (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2022)
Islamic educational thought has an important role in counteracting moral decline and identity crisis. This study aims to examine Zakiyah Darajat's thoughts in Islamic education. This literature-type study shows the result that Zakiah Daradjat's thoughts in the realm of Islamic education encourage the study of progressive environmental aspects of Islamic education. This result is driven by a conceptual study of Islamic education which according to him must support the balance of the world and the hereafter. This balance will have implications for human behavior in developing social relationships. He also concluded that lifelong education which covers all dimensions of life is expected to achieve his rights in this world and the rights in the hereafter. From these findings, this research contributes to the formation of a new concept of Islamic education that is in line with the development of the modern world.